ACHIEVEMENT OF LIPID TARGET PLASMA LEVELS IN PATIENTS OF HIGH CARDIOVASCULAR RISK: IS MEDICINE CHOICE IMPORTANT? - S. Y. Martsevich; N. P. Kutishenko (Столичная издательская компания, 2016)
The main indications to statins and principles of statin usage on the basis of International Guidelines are discussed. Problem of statin choice and problem of equivalence of generic drugs to original drugs are studied.